Socio-Economic Status of Migrants and their Household in Ranagaun - Panday, Tilak Raj (DMC Research Journal, 2018)
This study deals with socio-economic status of migrants and their households in Ranagaun representing varied socio-economic status. This study is based on primary data which are derived from field survey through questionnaires survey, field observation, in-depth interview and focus group discussion. For questionnaires survey 10 households are taken from migrant family in each ward with help of disproportionate stratified random sampling. Ranagaun VDC is one of poor VDC in Nepal. Labor migration is a major livelihood option in this area. It is one of the livelihood strategies of people. Most of the migrant workers from this area migrate to India, and the greater part of the remittances to this area is from India. However, the younger generation is increasingly migrating to countries in the Middle East, Southeast Asia, and the West. Remittances have a major impact on the welfare of recipient households, although the reliance on remittances varied among people depending on their wealth. Remittances are the main source of income for most people in the study area.